2023
DOI: 10.1111/jgh.16179
|View full text |Cite
|
Sign up to set email alerts
|

Role of rifaximin in the management of alcohol‐associated hepatitis: A systematic review and meta‐analysis

Abstract: Background and Aim Alcohol‐associated hepatitis (AAH) is an acute, inflammatory liver disease with severe short‐term and long‐term morbidity and mortality. AAH can lead to severe complications including hepatic failure, gastrointestinal bleeding, sepsis, and the development or decompensation of cirrhosis. Rifaximin is an antibiotic that reduces bacterial overgrowth and gut translocation, and it may have a role in decreasing systemic inflammation and infection in patients with AAH. Therefore, we conducted a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Studies on the use of prophylactic antibiotics in patients with AH have not shown promise for mortality benefit. In a placebo-controlled trial, rifaximin use for 90 days in patients with AH safely reduced infections (0.29 vs 0.62 infections/patient) and liver-related complications (0.43 vs 1.26 complications/patient) and showed a trend for lower 90-day mortality compared with the control arm (184,185). However, a 7-day course of oral vancomycin, gentamycin, and meropenem in 14 patients with AH showed no 90-day survival benefit compared with a reference group of patients with AH receiving standard of care (186).…”
Section: Ahmentioning
confidence: 97%
“…Studies on the use of prophylactic antibiotics in patients with AH have not shown promise for mortality benefit. In a placebo-controlled trial, rifaximin use for 90 days in patients with AH safely reduced infections (0.29 vs 0.62 infections/patient) and liver-related complications (0.43 vs 1.26 complications/patient) and showed a trend for lower 90-day mortality compared with the control arm (184,185). However, a 7-day course of oral vancomycin, gentamycin, and meropenem in 14 patients with AH showed no 90-day survival benefit compared with a reference group of patients with AH receiving standard of care (186).…”
Section: Ahmentioning
confidence: 97%